Patterns of sidemount four-bay FM antenna system - Gerino Mappatao (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper presents the radiation characteristics of a 4-bay collinear FM antenna system, both in free-space and with the presence of a metallic tower where the bays are mounted, with the use of powerful computers and accurate antenna simulation software. The radiation characteristics of the array are presented and discussed, such as the total gain, polarization components, circularity, beamwidth and minor lobe of the array. This is to determine the conformity of the array performance with existing standards. The possible effects of the metallic tower and the downward radiation from the minor lobe are emphasized. Being aware with these radiation characteristics, broadcast practitioners can optimize the use of this popular array. Results of numerical analyses show that the array is basically a vertically polarized radiator, the beamwidth is quite small which makes it disadvantageous for high-elevated antenna systems, the metallic tower affects the circularity of the azimuth pattern, and the downward radiation from the minor lobes can cause adverse effects. Adjustments on the basic elements and bay placements are recommended.